Synthesis of Lithium Mangan Oxide (LiMn2O4) Using Solution Method for Lithium Ion Battery Catodes Materials - Priyono, Slamet (Talenta Publisher, 2020)
Synthesis of Lithium Manganese Oxide (LiMn2O4) for Lithium Ion Battery Cathodes with Solution Method has been conducted. This experiment was carried out using the solution method. In this study, the synthesis was carried out by varying the calcination temperature. The raw materials used were Lithium Acetate (C2H3O2Li), Manganese Acetate (C4H6MnO4.4H2O), Hydrochloric Acid (HCl), and Ethanol (C2H5OH) as solvents which were dissolved to become LiMn2O4 precursors. Synthesis was carried out at calcination temperatures of 600oC, 700oC and 800oC, for 4 hours then pounded with a mortar until smooth. The characterization includes: The results of the STA test at 280oC-380oC showed a mass decrease of 11.9973% due to the release of mass of water vapor and decomposition of C4H6MnO4.4H2O raw material. XRD analysis shows that the increase in peak temperature of the LiMn2O4 phase intensity is getting sharper, the peak showing the impurity Li2O phase decreases. SEM analysis results show that the higher the calcination temperature, the larger the particle size is formed, because in the calcination process the densification process occurs.